John Boorman's The emerald forest [videorecording (DVD)] - Boorman, John, 1933-; Pallenberg, Rospo; Boothe, Powers, 1948-2017; Foster, Meg; Boorman, Charley; Polonah, Rui (MGM Home Entertainment, 2001)
Bill Markham, an engineer, returns to the Amazon year after year searching for his son who had disappeared into the jungle. After ten years of searching, Markham finds the man that had once been his boy, but now is a warrior from a different world.